2017
DOI: 10.1016/j.neuroscience.2016.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic PICK1 facilitates trafficking of AMPA-receptors between active zone and synaptic vesicle pool

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. AbstractPrevious studies have indicated that presynaptic -amino-3-hydroxy-5-methyl-4-isoxazole propionate receptors (AMPARs) contribute to the regulation of neurotransmitter release. In hippocampal synapses, the presynaptic surface expression of several AMPAR subunits, including GluA2, is regulated in a ligand dependent manner. However, the molecular mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…One study, however, reported that PICK1 did not bind Arp2/3 nor F-actin directly, but was involved in nondirectional organelle motility driven by myosin motors [ 129 ]. PICK1 was also involved in axonal trafficking via its newly identified partner the kinesin-binding protein syntabulin [ 130 ], which might, therefore, act as a motor protein for PICK1 regulation of presynaptic AMPAR trafficking [ 131 , 132 ]. Recently, PICK1 was also shown to interact with a central player in clathrin-mediated endocytosis, the adaptor protein AP2, which bridges cargo proteins and clathrin.…”
Section: Pdz Domain-containing Interactantsmentioning
confidence: 99%
“…One study, however, reported that PICK1 did not bind Arp2/3 nor F-actin directly, but was involved in nondirectional organelle motility driven by myosin motors [ 129 ]. PICK1 was also involved in axonal trafficking via its newly identified partner the kinesin-binding protein syntabulin [ 130 ], which might, therefore, act as a motor protein for PICK1 regulation of presynaptic AMPAR trafficking [ 131 , 132 ]. Recently, PICK1 was also shown to interact with a central player in clathrin-mediated endocytosis, the adaptor protein AP2, which bridges cargo proteins and clathrin.…”
Section: Pdz Domain-containing Interactantsmentioning
confidence: 99%
“…The regulated trafficking occurs upon induction of synaptic plasticity, leading to longlasting postsynaptic modifications. Differently, the constitutive trafficking develops in few minutes, independently on the synaptic activity and it occurs also presynaptically (30,39,40) where it mainly involves AMPA receptors composed of GluA2/ GluA3 subunits (44). Our results clearly indicate that the AMPA autoreceptors in cortical synaptosomes traffic in a constitutive manner, since hindering the GluA2/GRIP1/PICK1 with pep2-SVKI amplifies the (S)AMPA-mediated releasing activity.…”
Section: Discussionmentioning
confidence: 65%
“…The Western blot analysis of the cortical synaptosomal lysates unveiled the presence of the four GluA subunits (Figure 1). Each antibody recognized a component with a mass consistent with the monomeric form of the respective receptor subunit (~110 kDa) (38)(39)(40).…”
Section: The Glutamatergic Synaptosomes Isolated From the Cortex Of Amentioning
confidence: 99%
“…The immunogold labeling of sections of the hippocampal CA1 region with an anti-GluA2 antibody confirmed that the GluA2 subunit and PICK1 colocalized at the active zone. Moreover, the overexpression of GFP-PICK1 by the viral infection of organotypic hippocampal cultures significantly reduced the GluA2/3 immunogold labeling within the active zone and in the presynaptic cytoplasm [ 30 ]. These data suggest that PICK1 acts as regulator of presynaptic AMPAR trafficking.…”
Section: Ampar Localization At Presynapsementioning
confidence: 99%